Exercício físico, ingestão de frutose e marcadores da síndrome metabólica em modelo experimental - Botezelli, José Diego [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Metabolic Syndrome has become serious medical-social problem in developed and development country and the excessive fructose consumption in the occidental diet has a major role in this question. This way, it has been a great interest the development of procedures more effectives to prevent and treat this disease. The non-alcoholic fatty liver disease (NAFLD) emerges as a syndrome component and can be related to the development of insulin resistance. Once human studies have many limitations it is necessary the use of animal models adequate to this disease study. This research aims to investigate the potential effects of the physical exercise in the pathophysiology of fructose-induced metabolic syndrome, oxidative stress and inflammation. The first step aimed to analyses the effects of fructose-rich diet in metabolic syndrome markers. We used Wistar rats (120 days), separated in two groups, according to the diet: control (balanced Labina ® dieta) and fructose-rich diet (60% of caloric content provided by fructose). The animals fed on a fructose rich diet for 60 days (120-180 days). At the end of experiment, they were euthanized to determine in order: the glucose tolerance, insulin sensitivity, insulin levels, biomarkers of nonalcoholic fatty liver disease, biomarkers of oxidative stress and liver histology. The animals fed on fructose rich-diet showed lower glucose tolerance, insulin sensitivity, hiperinsulinemia, raises on serum glucose and triglycerides, higher AST/ALT ratio, fat accumulation in the liver and in the mesenteric adipose tissue, a reduction in the anti-oxidant system activities and higher levels of TBARs. The second step consisted to evaluate the effects of three exercise protocols in Wistar rats (120 days) on metabolic syndrome markers. Quarter of the animals were kept sedentary (C) during all the experiment (120-180 days); a quarter animals trained in the aerobic protocol (A) (80% of minimal lactate) 1h day, 5 days week,...

A síndrome metabólica tornou-se grave problema médico-social tanto em países desenvolvidos quanto em desenvolvimento e o consumo excessivo de frutose na dieta parece ter papel importante nessa questão. Dessa forma, é de grande interesse o desenvolvimento de procedimentos mais efetivos para prevenção e tratamento desta doença. Um dos procedimentos que merece investigação é o exercício físico. O presente estudo visou avaliar os efeitos singulares de três protocolos de exercício físico na prevenção e tratamento de complicações metabólicas desencadeadas por uma dieta rica em frutose. Numa primeira série de experimentos, visou-se analisar os efeitos de uma dieta rica em frutose sobre biomarcadores hepáticos e da síndrome metabólica em ratos. Foram utilizados ratos da linhagem Wistar que a partir dos 120 dias de idade, foram separados em dois grupos, conforme a dieta: controle (ração comercial para roedores labina ®) e frutose (dieta semipurificada com 60% de frutose). Ao final foram analisados tolerância à glicose (teste de tolerância oral à glicose), sensibilidade periférica à insulina (teste de tolerância à insulina), marcadores de esteatose hepática não alcoólica (EHNA) (concentrações séricas de alanina aminotransferase - ALT, aspartato aminotransferase - AST). Foram, ainda, determinados no fígado: concentrações de lipídios totais e de triglicerídeos, taxa de lipogênese hepática, biomarcadores do sistema de defesa antioxidante (atividade das enzimas catalase - CAT e superóxido dismutase - SOD) e de peroxidação lipídica (substâncias que reagem ao ácido tiobarbitúrico – TBARs) e histologia hematoxilina-eosina. Os animais alimentados com dieta rica em frutose apresentaram uma redução na tolerância à glicose, hiperinsulinemia, resistência à insulina, aumento na glicose e nos triglicerídeos circulantes, aumento na relação AST/ALT, acúmulo de gordura no fígado e no tecido adiposo...
Keywords: Physiology; Fisiologia; Exercícios físicos; Frutose; Síndrome metabólica; Disturbios do metabolismo; Obesidade; Marcadores biologicos; Stress oxidativo